MENGHITUNG INDEKS KEKUATAN NASIONAL - Posma Sariguna Johnson Kennedy (Buletin Ekonomi, 2018)
The concept of national power is very important and invites much debate. This paper aims to see how the national power of each country is calculated, so that it can be seen in its balance. This paper is based on literature study research method that see the development of every expert opinion in taking into account the national power. To see the balance of power required the calculation of national strengt, where each researcher sometimes gives a different way. Each country will compete to increase its strength, especially on economic resources.Keywords: national strength, national power index, national capability, economic power.